Mesopancreas: Myth or Reality? - Agrawal, Manish K; Thakur, Dilip Singh; Somashekar, Uday; Chandrakar, Shiv Kumar; Sharma, Dhananjaya (JOP. Journal of the Pancreas, 2010)
Context A recently published study hypothesized the concept of ‘mesopancreas’, defining it as a firm, well-vascularized structure extending from the posterior surface of the pancreatic head to behind the mesenteric vessels. Objective To verify and define mesopancreas from resection specimens obtained from fresh cadavers. Design Postmortem anatomical-pathological study. Setting Department of Surgery in conjunction with the Departments of Forensic Medicine and Pathology, Government Medical College and Hospital, Jabalpur, MP, India. Participants Twenty fresh adult cadavers without any intra-abdominal injury or gross intra-abdominal pathology. Interventions Specimens containing the entire duodenum, pancreatic head and neck, gallbladder, cystic duct, common bile duct, superior mesenteric vessels, inferior vena cava and aorta were removed en-bloc. Gross and histopathological examinations of the specimens were carried out. Main outcome measures To look for a fibrous sheath or fascia around the retropancreatic structure purported to be a mesopancreas. Results Loose areolar tissue, adipose tissue, peripheral nerve, nerve plexus, lymphatic and capillaries were found in the retropancreatic tissue, extending from the head, neck and uncinate process of pancreas to the aorto-caval groove but no fibrous sheath or fascia was found around these structures. Conclusions The concept of ‘mesopancreas’ is anatomically unfounded. Image: Anterior view of the resected specimen.